Improving the Literacy of the Nagari Community on Public Administration in National and State Life in the West Sumatra Province. - Assyahri, Wahib; Indry, Indry; Bila, Aziza; Oktaviane, Diga Putri (MARAWA: Jurnal Masyarakat Religius dan Berwawasan, 2023)
Administration is often only seen as a writing activity. Physically, administrative activities are dominated by writing activities, even though there are many theories that say administrative activities are more than that. Public administration seeks how the collective government administration process becomes a management government activity (planning, organizing, implementing, supervising development) with work mechanisms and human resource support and administrative support or governance. The implementation method that will be carried out in this community service is at the pre-implementation stage, namely the socialization of activities in the community and the implementation stage, namely the implementation of community empowerment program activities held on August 11, 2023 online through community service seminar web activities. The results of this service are increasing literacy and increasing the knowledge of the nagari community about public administration with a series of activities, namely counseling with the main objective of providing descriptions of the essence of public administration science, the development of public administration science, the challenges of public administration science and public administration strategies facing advances in information technology.